Prevalence of Obesity among Students in Private and Public high Schools in Sulaimani City - Kawa Hama Salih, Khuncha; Jawhar Ali, Solaf; Mohammed Amin Ahmed , Ahmed (Diyala Journal of Medicine, 2023)
Background: There is an increasing concern about obesity among children and adolescents worldwide as they constitute 20% of the world population. Several predisposing factors are contributing to the obesity that can be monitored, particularly healthy diet and physical activities. Addressing those factors among children and adolescents lead to decreasing health related conditions. Objective: To investigate the prevalence rate of obesity, sociodemographic, dietary habits, lifestyle and knowledge factors among adolescents attending private and public schools in Sulaimani city, Iraq. Patients and Methods: Through a school-based cross-sectional study from October 2021 to April 2022, a total of 576 students in high schools located in Sulaimani city, Kurdistan Region, Iraq were studied. A structured questionnaire was used to collect information on students’ sociodemographic characteristics, physical activities, dietary habits and knowledge. Body mass index was measured based on WHO Growth Reference for 5 to 19 years of age. Results: The obesity prevalence rate in private schools (36.11%) was higher than public schools (31.6%) (P=0.5890) however, the difference was not statistically significant. The majority of students in private schools exercised more frequently and for a longer duration; however, they ate more red meat, less dairy produce and had a higher fast food intake. Conclusion: The prevalence of obesity is slightly higher among students in private schools than the students in public schools.